心筋特異的Bcl-2–associated athanogene (BAG) 3欠損マウスの心機能と生存率に対するニコランジルの効果 - 高橋, 夏美; 河野, 竜一郎; 佐藤, 幸子; 弘瀬, 雅教; 三部, 篤; 小原, 真美; 平, 英一 (日本薬理学会年会要旨集, 2023)
Bcl-2–associated athanogene (BAG) 3 is known as a regulator of cell death as well as autophagic protein turnover in the heart, and disruption of the BAG3 gene in a cardiac-specific manner can lead to cardiac failure in mice. However, little is known about therapeutic approaches to the cardiac failure induced by BAG3 disruption. We characterized mouse ablated BAG3 gene using a Cre-recombinase-loxp site system in a cardiac-specific manner (BAG3f/f crossbred with Cre transgenic mice; BAG3 cKO) and examined the therapeutic effect of nicorandil in BAG3 cKO mice. Cardiac BAG3 level was markedly attenuated in BAG3 cKO mice compared with hearts of BAG3f/f mice. BAG3 cKO mice showed evidence of cardiac disease, including a reduction in fractional shortening detected by echocardiography, as well as cardiac fibrosis at 6 months of age. BAG3 cKO mice also showed premature death (~40%) up to 6 months of age. Mice were treated with nicorandil (81 mg/L drinking water) beginning at 1 month of age. Nicorandil treatment was able to prevent the reduction of fractional shortening, cardiac fibrosis, and premature death. Thus, although the underlying molecular mechanisms remain unclear, long-term treatment with nicorandil appears to inhibit cardiac disease induced by cardiac-specific BAG3 ablation.